(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The article explores the «children’s» heritage of the famous Ukrainian writer Ivan Bahrianyi. From the positions of the genre and stylistic peculiarities were consid-ered of the poetic tales of «Telephone» and «Tale of the Storks and Pavlik-traveler», short story «To Vorskla, to fish», rhymes «Engineer», «Impromptus» and the song «Lullaby» in the context of the writer’s own creativity and in the context of the epoch.